Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 1993
DOI: 10.1115/93-gt-118
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and Temperature Distortion Testing of a Two-Stage Centrifugal Compressor

Abstract: Altitude pressure and temperature inlet distortion testing of the two-stage centrifugal compressor in the T800-LHT-800 engine is described. The test setup and the testing techniques are reviewed and the results of the test are presented. The generation of classical 180 degree patterns of both pressure and temperature distortion is discussed. Temperature distortion was created using a hydrogen burner system while pressure distortion was created in the classical manner, using screens. Results of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…Flow nonuniformity at the impeller inlet, which is generally known as ''inlet distortion'', has been investigated with experiments and numerical simulations to analyze the effects of inlet distortions on centrifugal compressors. [2][3][4][5][6][7] The investigations indicated that inlet distortions mainly influenced the performances of centrifugal compressors by introducing nonuniform pressure and flow angle distributions to the impeller inlet, which could cause incidences, boundary layer separations and possibly rotating stall of impellers.…”
Section: Introductionmentioning
confidence: 99%
“…Flow nonuniformity at the impeller inlet, which is generally known as ''inlet distortion'', has been investigated with experiments and numerical simulations to analyze the effects of inlet distortions on centrifugal compressors. [2][3][4][5][6][7] The investigations indicated that inlet distortions mainly influenced the performances of centrifugal compressors by introducing nonuniform pressure and flow angle distributions to the impeller inlet, which could cause incidences, boundary layer separations and possibly rotating stall of impellers.…”
Section: Introductionmentioning
confidence: 99%